Do alkali metal anions (M(-)) exist in zeolite A? - Barker, P; Anderson, P; Dupree, R; Kitchin, S; Edwards, P; Woodall, L (Materials Research Society, 1996)
Recent NMR studies by Nakayama et al. on sodium zeolite A saturated with potassium metal have implied the presence of the anionic Na- species. This, if confirmed, would represent the first observation in a zeolite and opens up a wide range of possibilities for mixed metal zeolitic systems. We report the results of a number of metal combinations, using both sodium and potassium forms of zeolite A as hosts, studied by ESR, solid state MAS-NMR and powder neutron diffraction.